Evaluation of efficacy of rehabilitation program administered to patients with incidence of gastric and duodenal ulcers - Очередько, Александр Николаевич; Кизлова, Наталия Николаевна (ScienceRise: Medical Science, 2016)
Duodenal (DU) and gastric ulcer (GU) experience their rise in Ukraine, demonstrating threatening increase by 38,4 % in last decade with the prevalence of 2299 per 100 000 of population. Every second patient is treated in-patiently, every third experience disability spell annually. Reduction in related risks is confirmed not only by absence of effective therapy, but rather shortcomings in patient management and patient devotion. General belated timing of rehabilitation initiation in post hospital stage appeared to be cardinal obstacle of its efficiency with low (up to 20 %) coverage, and securing clinical effect in 8 % cases only. The goal was to evaluate efficacy of rehabilitation program detailed at first episode of in-patient treatment at gastroenterological department. Methods. Data were organized by cohort design. Control cohort comprised 180 patients with first episode of hospitalization due to DU or GU in gastroenterological Vinnitsa city department during 2009–2012 years. Experimental cohort consisted of 220 equal patients who entered rehabilitation program (RP). RP was administered randomly. Randomness was statistically verified on principal confounders. Cases were traced for 4 years. We applied three modifications of semi-parametric frailty model to study effect of program on the risk of recurrent hospitalization. Results. All three modifications coincided in that program secured typically at least 39 days to recurrent hospitalization per patient with drop in risk at least at RR=0,774. Conclusion. To reduce belated timing of rehabilitation initiation, we shifted administration of rehabilitation to hospital stage. RP frame combines 10 scales, namely medication of ulcer, diet modification, overweight control, physiotherapy exercises, NSAID-induced gastropathy control management, risk factor management, blood pressure correction, diabetes management, anxiety and depression management. Program efficacy estimation relied upon time to recurrent hospitalization, which proved to be very sensitive to quality of care. Results of three survival model modifications coincided in that program secured typically at least for 39 days to recurrent hospitalization per patient with drop in risk at least at RR=0,774